Identification of MPL R102P Mutation in Hereditary Thrombocytosis - Bellanné-Chantelot, Christine; Mosca, Matthieu; Marty, Caroline; Favier, Rémi; Vainchenker, William; Plo, Isabelle (Frontiers in Endocrinology, 2017)
The molecular basis of hereditary thrombocytosis are germline mutations affecting the thrombopoietin (TPO)/TPO receptor (MPL)/JAK2 signaling axis. Here, we report one family presenting two cases with a mild thrombocytosis. By sequencing JAK2 and MPL coding exons, we identified a germline MPL R102P heterozygous mutation in the proband and his daughter. Concomitantly, we detected high TPO levels in the serum of these two patients. The mutation was not found in three other unaffected cases from the family except in another proband’s daughter who did not present thrombocytosis but had a high TPO level. The MPL R102P mutation was first described in congenital amegakaryopoiesis thrombocytopenia (CAMT) in a homozygous state with a loss-of-function activity. It was previously shown that MPL R102P was blocked in the endoplasmic reticulum without being able to translocate to the plasma membrane. Thus, this case report identifies for the first time that MPL R102P mutation can differently impact megakaryopoiesis: thrombocytosis or thrombocytopenia depending on the presence of the heterozygous or homozygous state, respectively. The paradoxical effect associated with heterozygous MPL R102P may be due to subnormal cell-surface expression of wild-type MPL in platelets inducing a defective TPO clearance. As a consequence, increased TPO levels may activate megakaryocyte progenitors that express a lower, but still sufficient level of MPL for the induction of proliferation.